2004
DOI: 10.3758/bf03196723
|View full text |Cite
|
Sign up to set email alerts
|

An event-related potential study of the revelation effect

Abstract: Event-related potentials (ERPs) were recorded during a verbal recognition memory task in order to investigate whether changes in familiarity are part of the explanation for the revelation effect. For half of the test words, participants solved an anagram prior to making the old/new recognition judgment. A revelation effect was obtained: When test words were preceded by the anagram task, a higher probability of an old response was associated with the items than was otherwise the case. The ERPs recorded time-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…They argued that anagrams can yield many solutions; the signal-tonoise ratio for the target word is reduced, increasing the difficulty of the recognition task. Participants respond to this increased difficulty by adopting a liberal criterion for their recognition decision (see also Azimian-Faridani & Wilding, 2004). Niewiadomski and Hockley (2001), however, reported revelation effects of similar size regardless of whether arithmetic problems or anagrams are used.…”
Section: Discussionmentioning
confidence: 99%
“…They argued that anagrams can yield many solutions; the signal-tonoise ratio for the target word is reduced, increasing the difficulty of the recognition task. Participants respond to this increased difficulty by adopting a liberal criterion for their recognition decision (see also Azimian-Faridani & Wilding, 2004). Niewiadomski and Hockley (2001), however, reported revelation effects of similar size regardless of whether arithmetic problems or anagrams are used.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity, measured as activity in the anterior, frontal scalp region 300-500 ms after the onset of the test item, is lower after a preceding task than without a preceding task (Azimian-Faridani & Wilding, 2004). Later research, however, found this data pattern only when the task item was identical to the test item, not when it was different (Leynes, Landau, Walker, & Adante, 2005).…”
Section: Evaluation Of Hypothesesmentioning
confidence: 93%
“…Two of the questions emphasized word sound, The criterion-shift accounts do so indirectly. In terms of the dual-process account, criterion-mediated decisions are assumed to be relevant only for familiarity-based responding (Azimian-Faridani & Wilding, 2004;Leynes et al, 2005;Yonelinas, 2002). Despite differences between the accounts, all of these accounts imply that revelation influences familiarity-based memory decisions but not recollection (Azimian-Faridani & Wilding, 2004;Cameron & Hockley, 2000).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…As described in the introduction, the present experiments were designed to test the common dual-process implication that revelation exerts its effects on familiarity-based responding (e.g., Azimian-Faridani & Wilding, 2004;Cameron & Hockley, 2000), rather than to make a finegrained distinction between accounts proposing direct changes to familiarity vs. criterion shift. However, when revelation influenced performance, it influenced c (a standard measure of criterion placement) rather than d (discriminability), a result consistent with criterion-shift accounts (Verde & Rotello, 2004).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation